(untitled) (Revista Educação, Artes e Inclusão, 2022)
The present work proposes an analysis of the curriculum of the Vocational Technical Course in Dance at Colégio Modelo Luís Eduardo Magalhães in Itabuna, Bahia, based on critical theories and on the emancipatory ideas of Paulo Freire, in order to identify the existence of content chosen according to the mechanisms of domination arising from coloniality. In addition, the research alerts to the urgency of building practices that decolonize the curriculum for a professional technical training in Dance based on respect for cultural diversity. The research, regarding its approach, is qualitative; as to its nature, basic; as for the objectives, exploratory; and as for the procedures, bibliographical. To carry out the research, recent theories of science that deal with Education (FREIRE, 1967; 1987; 1989; 1996), Dance (SANTOS, 2009) (SETENTA, 2017), Biopolitics (FOUCAULT, 1987; 1988; 1999) were analyzed (AGAMBEN, 2009), Curriculum (RANGHETTI; GESSER, 2009) (SILVA; 2010) and decolonial thinking (COSTA; 2006) (GOMES, 2012) (KILOMBA, 2019) (MBEMBE, 2016). It was concluded that the mentioned curriculum was not elaborated from a participatory, collaborative construction, and that its logic is still Eurocentric.